Evaluasi Tentang Pemungutan Pajak Bumi Dan Bangunan Sebagai Pendapatan Pajak Daerah Di Kota Jambi - Muhrizal Muhrizal; Johandri Iqbal; Pramesti Nurul Adinda (LP2M Politeknik Jambi, 2024)
The influence of the evaluation of land and building tax collection carried out by the government in carrying out its rights and obligations as a fiscus, especially in the regional sector of Jambi City entitled